The Effect of Emotional Labor on Presenteeism of Chinese Nurses in Tertiary-Level Hospitals: The Mediating Role of Job Burnout - Song, Jia; Liu, Fang; Li, Xiaowei; Qu, Zhan; Zhang, Rongqiang; Yao, Jie (Frontiers in Public Health, 2021)
Background: Employees who are physically present but work insufficiently because of illness are deemed as having presenteeism. In the health care setting, the issue has taken on greater importance because of impaired nurses’ physical and mental health and patients’ nursing safety. According to the Job Demand-Resource Model, burnout may link emotional labor with presenteeism. This study analyzes the role of burnout as a mediating factor between three types of emotional labor strategies and presenteeism among nurses in tertiary-level hospitals. Methods: A cross-sectional study of 1,038 nurses from six Chinese hospitals was conducted. The questionnaire, including emotional labor strategies, burnout, and a presenteeism scale, was used to collect data. Results: Participants’ average presenteeism score was 14.18. (4.33), which is higher than in Spanish, Portuguese, and Brazilian nurses. Presenteeism was explained by 22.8 % of the variance in the final model in multi-variables linear regression (P < 0.01). Presenteeism was found to be positively correlated with surface acting, emotionally expressed demands, deep acting, emotional exhaustion, depersonalization, and low personal accomplishment (P < 0.01). Notably, presenteeism was negatively correlated with deep acting (P < 0.01). In addition, burnout partially mediates the correlation between emotionally expressed demands, deep acting and presenteeism with a mediatory effect of 24% and 63.31% of the total effect; burnout completely mediates the association between surface acting and presenteeism, a mediating effect of 86.44% of the total effect. Conclusions: Our results suggest that different emotional labor strategies affect presenteeism, either directly or indirectly. Nursing managers should intervene to reduce presenteeism by improving nurses’ ability to manage emotions, thereby alleviating burnout.